A facile method for scalable synthesis of ultrathin g-C3N4 nanosheets for efficient hydrogen production. Issue 37 (13th September 2018) - Zhang, Jian-Hua; Hou, Ya-Jun; Wang, Su-Juan; Zhu, Xunjin; Zhu, Cheng-Yi; Wang, Zheng; Li, Chao-Jie; Jiang, Ji-Jun; Wang, Hai-Ping; Pan, Mei; Su, Cheng-Yong
Abstract : Scalable production of ultrathin g-C3 N4 nanosheets for efficient water splitting by the aid of kitchen-available melamine foam (MF). Abstract : 2D graphitic carbon nitride (g-C3 N4 ) has attracted great attention as one of the rising-star candidates for prominent water-splitting photocatalysts. Here, we report an extremely facile one-step, template-free method to synthesize ultrathin g-C3 N4 nanosheets (CN-UMF) by thermal polycondensation of urea simply covered with kitchen-available melamine foam (MF). Compared with g-C3 N4 agglomerates (CN-U) prepared without the covering of MF, the as-synthesized CN-UMF has an average thickness of about 4.5 nm and an enlarged surface area of 150.3 m 2 g −1, leading to enhanced visible light absorption and charge carrier separation abilities. Therefore, it is able to serve as an efficient water-splitting photocatalyst to result in an outstanding hydrogen production rate of 5498 μmol g −1 h −1 . This work provides a new facile strategy for the scalable synthesis of 2D g-C3 N4 photocatalysts and paves the way for batch and green production of other 2D materials with good performance.